2010
DOI: 10.1111/j.1466-8238.2010.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

No biogeographical pattern for a root‐associated fungal species complex

Abstract: AimThe biogeography of microbes is poorly understood and there is an open debate regarding if and how microbial biodiversity is structured. At the beginning of the 20th century, Baas Becking laid the foundations for the biogeography of microbes by stating that 'Everything is everywhere, but the environment selects' (the EisE hypothesis). This hypothesis remained dogma for almost a century. However, the recognition that microbial 'species' are often assemblages of reproductively isolated lineages challenged the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 62 publications
7
80
4
Order By: Relevance
“…However, these correlations do not necessarily represent the direct links between plants and microorganisms, and the empirical evidence of direct links appears to be inconclusive (Waldrop et al, 2006;Bryant et al, 2008;Queloz et al, 2011;van der Putten et al, 2013). In fact, hosts per se had little predictive power with regard to the EM fungal composition in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these correlations do not necessarily represent the direct links between plants and microorganisms, and the empirical evidence of direct links appears to be inconclusive (Waldrop et al, 2006;Bryant et al, 2008;Queloz et al, 2011;van der Putten et al, 2013). In fact, hosts per se had little predictive power with regard to the EM fungal composition in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these are assigned to Phialocephala fortinii s.l. -Acephala applanata species complex (PAC) that constitute the bulk of DSE communities colonizing conifers and Ericaceae in the Northern Hemisphere including Europe, North America, and Asia (Jumpponen and Trappe 1998a ;Grünig et al 2008b ;Queloz et al 2011 ;Walker et al 2011 ). Second , thus far no evidence has been presented for an interface that would facilitate nutrient exchange between the host and its DSE symbionts (Petersen et al 2008 ).…”
Section: Introductionmentioning
confidence: 98%
“…For example, negative feedbacks are generally thought to depend on high levels of variability in the strength of plant-fungal interactions and on strong spatial heterogeneity in fungal community composition (Gilbert, 2002). However, theoretical (May, 1991) and empirical Smith et al, 2011Smith et al, , 2013) studies have suggested low levels of fungal host specificity in tropical forests, and many studies have questioned the importance of dispersal limitation in microbes (Finlay, 2002;Queloz et al, 2011). Detailed knowledge on the structure of fungal communities is thus necessary to guide research to answer these critical ecological questions.…”
Section: Introductionmentioning
confidence: 99%